SPEECH ACTS DALAM SERIAL TV GAME OF THRONES: KAJIAN PRAGMATIK - Tumimomor, Christian T; Imbang, Djeinnie; Kalangi, Leika M V. (Universitas Sam Ratulangi, 2019)
AbstractÂ This research focused on the illocutionary acts in Game of Thrones TV series. It aims to have a description of the illocutionary acts and to identify the utterances with its meaning in the show. In this study the data were analyzed through qualitative analysis, the data collected in this research are from the showâ€™s script of Game of Thrones Season 6 episode ten entitled â€œThe Winds of Winterâ€. The data are categorized and explained based on Austinâ€™s classification of illocutionary acts as the pioneer of this theory. The results of the data analysis showed that the illocutionary acts performed by the characters in the series are varies and included in Austinâ€™s classification of illocutionary acts which are verdictives, excersitives, commissives, behabitives and expositives. Based on the results, the illocutionary acts performed by the characters in the series are influenced by the speakerâ€™s or the addresseeâ€™s status, it is indicated by how the nobles performed their illocutionary acts are different comparing to the peasants in the show. It could be concluded that the speakerâ€™s background or status are influential when performing illocutionary acts and to gain proper response from the addressee.Key words: speech acts, illocutionary acts, game of thrones.